2020
DOI: 10.1002/mgg3.1306
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic spectrum and antialbuminuric response to angiotensin converting enzyme inhibitor and angiotensin receptor blocker therapy in pediatric Dent disease

Abstract: Background To characterize the phenotypic spectrum and assess the antialbuminuric response to angiotensin converting enzyme (ACE) inhibitor and/or angiotensin receptor blocker (ARB) therapy in a cohort of children with Dent disease. Methods The patients’ clinical findings, renal biopsy results, genetic and follow‐up data were analyzed retrospectively. Mutations in CLCN5 or OCRL were detected by next‐generation sequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 27 publications
(20 reference statements)
0
6
0
1
Order By: Relevance
“…The reduction in albuminuria levels seen in some DD1 and DD2 patients may be due to the action of RAAS blockers on the proteinuria originating from glomerular damage. This is the picture that emerged in a study by Deng et al on children with Dent disease, despite a decrease in albuminuria levels being reported in only half of those with confirmed glomerular disease (Deng et al 2020). ACEi/ARBs are generally well tolerated by children with Dent disease.…”
Section: Therapymentioning
confidence: 92%
See 2 more Smart Citations
“…The reduction in albuminuria levels seen in some DD1 and DD2 patients may be due to the action of RAAS blockers on the proteinuria originating from glomerular damage. This is the picture that emerged in a study by Deng et al on children with Dent disease, despite a decrease in albuminuria levels being reported in only half of those with confirmed glomerular disease (Deng et al 2020). ACEi/ARBs are generally well tolerated by children with Dent disease.…”
Section: Therapymentioning
confidence: 92%
“…These extrarenal clinical signs are to be expected, but are not always seen in patients with DD2 (Table 2). On the other hand, congenital cataract and intellectual disability were also described in children with DD1 in whom next-generation sequencing (NGS) studies revealed no OCRL mutations (Deng et al 2020;Sakakibara et al 2020). Dent disease patients are also usually referred to a nephrologist rather than a neurologist (unlike Lowe syndrome patients), so cognitive defects might go unreported, leading to an incomplete description of the clinical phenotype (Bökenkamp et al 2009).…”
Section: Clinical Signs Of Dent Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…The proteinuria was not relieved after the treatment, which was consistent with previous reports ( 21 ). It has been reported that angiotensin converting enzyme inhibitors (ACEI) drugs could reduce the urinary protein excretion in patients with type 1 Dent disease ( 6 , 22 ). On the other hand, Vaisbich et al did not find benefit from ACEI therapy in patients with type 1 Dent disease ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thiazide diuretics can decrease urinary calcium excretion in males with DD1, but side effects are common. 2 Angiotensin-converting enzyme inhibitor and angiotensin receptor blocker therapies have been tried to ameliorate proteinuria, 13 but do not target the molecular etiology of DD1 and cannot stop its progression. A therapy that targets the molecular etiology is needed for better therapeutic effects.…”
Section: Introductionmentioning
confidence: 99%